Interest in Students' Entrepreneurship Building Engineering Education Program - Putri Lynna Adelinna Luthan; Nathanael Sitanggang; Choms Gary Ganda Tua Sibarani (Universitas PGRI Semarang, 2023)
The purpose of this study to determine the interest in entrepreneurship and factors inhibiting entrepreneurship for students. The study was conducted on Education courses State University Of Medan Building Engineering, Faculty of Engineering in 2019. The research method is a method of ex post facto. The sampling technique is purposive random sampling and using Taro Yamane formula. Sample of 118 students who have attended entrepreneurship courses. The instrument used was a closed questionnaire Likert scale with a reliability coefficient of 0.90 and for the deepening of the data used an open questionnaire. The data analysis technique used descriptive statistics. Results found is the tendency of student interest in entrepreneurship Building Engineering Education courses classified as high category (66%), and 2.54% of the students have entrepreneurship. The high interest in entrepreneurship students also reflected on the desire of students to start college entrepreneurship (20.34%). Nevertheless, interest in entrepreneurship students of Building Engineering Education will remain a concern professors and functionaries in the Faculty of Engineering make efforts to increase student interest in entrepreneurship because there is still a 34% student interest in entrepreneurship classified as a low category. The results of this study are very beneficial to universities and professors to improve the quality of teaching entrepreneurship courses.